A journey to the center of the earth - Verne, Jules, 1828-1905 (Great illustrated classics, 2002)
Professor Hardwigg, his nephew Harry, and their guide Hans explore a volcanic crater in Iceland that leads them to the center of the Earth and to incredible and horrifying discoveries.